Exhibition Space Management of Chiharu Shiota as Museum MACAN's Becoming a Child-Friendly Museum - Tiara Isfiaty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This article aims to describe the child-friendly management of Chiharu Shiota's exhibition space at MACAN museum. Museum collections are a medium of information for the audiences who see them. One of the museum's audience groups is children. The management of collections in an exhibition is an important factor in directing visitors, especially children, to get the right information when understanding and learning about museum collections. The management of museum collections involves visual media outside the collection objects. The visual media in question is labeling, which is a medium that contains a variety of information about complementary information from the collection of artifacts on display at the Museum. In the context of a child-friendly museum, labelling has a major role in guiding a child when viewing and understanding a collection object. The research was conducted using direct observation method to the field. Researchers observed and documented the visual medias that accompany the collection objects and how to place them in a MACAN museum showroom. The results of the research are expected to be an alternative framework for managing the collection of an exhibition in a museum in the context of a child-friendly museum. This is in line with the museum's function as an out-of-school educational facility for children